2014
DOI: 10.2478/pjvs-2014-0045
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of serum levels of allergen-specific immunoglobulin E in different seasons and breeds in healthy horses

Abstract: The present study was designed to asses specific IgE towards environment allergens in 42 healthy horses. Determination of this immunoglobulin in serum serve as diagnostic tools in allergic diseases to improve efficacy of the treatment and proper allergen selection to specific immunotherapy. Serum levels of allergen specific IgE were measured with equine monoclonal antibody, using 15 individual and 5 mix allergens in North European Panel. The study revealed season dependent increased levels of allergen specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…The factor that contributed most to the occurrence of allergies among the horses was house dust mites (D. farinae), which were diagnosed in 18 animals (64.3%). The high prevalence of mite allergens found in other studies (Tahon et al, 2009;Wilkołek et al, 2014) may be because of the pellets and grains used in horse feed that contains large amounts of forage mites. In the present study, horses had straw bedding and thus had ongoing contact with mites.…”
Section: Resultsmentioning
confidence: 75%
See 2 more Smart Citations
“…The factor that contributed most to the occurrence of allergies among the horses was house dust mites (D. farinae), which were diagnosed in 18 animals (64.3%). The high prevalence of mite allergens found in other studies (Tahon et al, 2009;Wilkołek et al, 2014) may be because of the pellets and grains used in horse feed that contains large amounts of forage mites. In the present study, horses had straw bedding and thus had ongoing contact with mites.…”
Section: Resultsmentioning
confidence: 75%
“…xx with prevalence ranging from 0% to 74% depending on the region (Wilkołek et al, 2014;Mueller et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Each of these could have impacted on the level of allergen exposure and therefore the likelihood of reactivity and co‐reactivity being demonstrated. A Polish study investigating environmental allergen‐specific IgE responses in healthy horses found marked seasonal variation in reactivity levels . A similar seasonal effect was not, however, demonstrated in horses with IBH, leading to the hypothesis that in allergic horse's the plasma cells may continuously produce IgE without B‐cell reactivation …”
Section: Discussionmentioning
confidence: 99%
“…However, false-negative results can occur in asymptomatic period. IDT was performed in fall and winter during asymptomatic period of the disease [27]. Though, the greatest severity of symptoms associated with allergies to dust mites occurs in summer and autumn, however, symptoms may occur year-round [18].…”
Section: Discussionmentioning
confidence: 99%